Urban Centers: Memorandum. Document produced for the Horizon 2020 project ‘ROCK’ - Falanga, Roberto (2020)
This Memorandum is a policy-oriented research document conducted by the ICS-ULisboa team of the Horizon 2020 project ROCK. It seeks to organise some of the most up-to-date knowledge around Urban Centers and highlight important discussion topics, requiring further attention. In addition to academic literature review, the Memorandum relies on contributions from the international conference “Urban Centers: Acting upon or with cities?” organised by the ICS-ULisboa on the 19th October 2018 (https://rockproject.eu/event-details/41). The Conference took place in the Centre for Urban Information of Lisbon with the participation of representatives from the following Urban Centers: Centro de Informação Urbana de Lisboa (Lisbon); Fondazione Innovazione Urbana (Bologna); Urban Center of Torino; Pavillon de L’Arsenal (Paris); Centro de Cultura Contemporània Barcelona; and casa della Città / Case del Municipio (Rome). The participating Urban Centers were selected from the list provided by the international laboratory on Urban Centers (http://www.urban-center.org/en/), on the basis of their different working contexts, management models and activity. Representatives were invited to share knowledge and experience about the role, the challenges and potential of Urban Centers today and the different forms of action and participation they may have in the development of their cities.